Concurrent multi-scale optimization of hybrid composite plates and shells for vibration. (1st February 2020) - Ma, Xiangtao; Tian, Kuo; Li, Hongqing; Zhou, Yan; Hao, Peng; Wang, Bo
Abstract: In this paper, a concurrent multi-scale optimization framework is established for hybrid composite plates and shells, where fiber volume, fiber orientation and stacking sequence can be optimized simultaneously. Firstly, a finite element model of shell structure that contains patches is established. Then, the candidate material set of hybrid composites is calculated and assembled by different combinations of fiber volume, fiber orientation and stacking sequence at the material and laminate scales. Furthermore, the Discrete Material Optimization (DMO) method is employed to perform the concurrent multi-scale optimization. Two illustrative examples are used to verify the effectiveness of the proposed optimization framework, including a simple example of a hybrid composite plate and a complex engineering example of a double serpentine nozzle. In comparison to optimal results by the traditional constant-stiffness design method, the optimal results of the proposed framework achieve significant 19.8% and 14.0% improvements in the fundamental frequency under the constraint of material cost, respectively. It can be concluded that the proposed concurrent multi-scale optimization framework has huge potential in adaptive stiffness tailoring for hybrid composite plates and shells with complex multi-scale design variables, which can make full use of hybrid composite materials to improve the structural performance against vibration while maintaining the low material cost.